Name, Shame, and Then Build Consensus? Bringing Conflic Resolution Skills to Human Rights - Stephan Sonnenberg; James L. Cavallaro (Washington University Journal of Law & Policy, 2012)
This Article examines the reasons behind the tensions that continue to make integration of human rights theory and dispute resolution so difficult. It seeks to interrogate the status quo, with a focus on law school clinics. We believe that many complex human rights problems that would traditionally be addressed separately by human rights and dispute resolution practitioners would benefit from a more integrated approach. As a consequence, the training of practitioners would also benefit from a pedagogy that incorporates elements of both disciplines. By taking a step back from the existing structure of clinics and turning to the goals that they seek to achieve, we argue for a new model that brings together skills and approaches from traditional human rights and conflict resolution approaches to develop a hybridized model of practice.12 This Article recognizes the inroads that human rights discourse and practice have already made in conflict resolution. It thus focuses primarily on the contributions that conflict resolution can make to human rights approaches. This year, at Stanford Law School, the authors of this Article have begun the process of launching just such a human rights and conflict resolution clinic. This Article seeks to explain the background, objectives, and future prospects for this and similar clinics. The Article considers three representative case studies. These cases come from the authors‘ personal experience working in Non- Governmental Organizations (NGOs) or clinics devoted to either human rights or conflict resolution. We chose the examples not only to illustrate typical scenarios in which a hybridized practice of human rights and conflict resolution proved to be either absent or effective, but also to highlight three prominent tensions that we believe any human rights project incorporating conflict resolution skills will face: (1) the tension between skepticism vs. optimism; (2) the tension between signaling strength vs. inviting collaboration; and (3) the tension between maintaining relationships vs. demanding critical selfanalysis. Our analysis of the three case studies provides a description of how we managed these tensions in our projects and proposes several benefits from the perspective of a human rights practitioner on an integrated approach. The Article concludes by outlining the structure and pedagogy of our clinic, the type of projects we select, and the ways we hope to document our success (and shortcomings) as the years progress.
Keywords: Clinical legal education; Dispute resolution (Law); Human rights; Law school; Case studies; Stanford Law School; Conflict management; Conflict resolution; Dispute systems design (DSD); Legal profession; Interests